Green Catalysts Activities of CaO Nanoparticles from Pinctada maxima Shell on Alcoholysis Reaction - Kendri Wahyuningsih; Jumeri Jumeri; Wagiman Wagiman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Pinctada maxima shells from West Nusa Tenggara has natural minerals called calcite that can be decomposed into CaO compounds as a green catalyst that heterogeneous, base and environmentally friendly. CaO compounds in the nanometer scale is one option as an alternative substitute or replacement of the use of homogeneous catalysts. The purpose of this study was to test the catalytic activity of CaO compound from the pearl shells (P. maxima) based on particle size. The catalytic activity test has been measured against the percentage of yield of methyl ester produced by alcoholysis reaction. Characterization of nano-CaO compounds has been done using X-ray powder diffraction (XRD), Brunauer Emmett Teller (BET), scanning electron microscope energy-dispersive X-ray spectroscopy (SEM-EDX), transmittance electron microscopy (TEM), while methyl esters has been analyzed using the ASTM method. CaO catalyst on the nanometer-scale have more effective catalytic activity than micrometer scale with the yield percentage of methyl ester obtained are 81,61% and 30,71%, respectively. The results of methyl ester characterization by ASTM method has shown that methyl ester has specification that are close to diesel oil, so it can be used as an alternative or substitution on diesel engine.